La réaction sociale à la délinquance juvénile : une analyse stigmatique - LeBlanc, Marc (Acta Criminologica)

(untitled) (Les Presses de l'Université de Montréal, 1971)
AbstractJUVENILE DELINQUENCY AND SOCIAL REACTIONThe object of this research is to define the process of social reaction to juvenile delinquency, as well as the criteria used by the agencies of social control in deciding what factors brand the adolescent a delinquent. Starting with self-reported delinquency, we follow its course within the system of social regulations practised by the public, the police and the courts.The data concern self-reported delinquency (measured by the questionnaire of Nye and Short on self-reported delinquency), delinquency officially known to the police, and the decisions taken by the police and judges with regard to delinquent acts. These data were gathered in five districts in Montreal, representing five social strata.The analysis of the stigma of delinquency showed that there is more chance of working-class subjects entering the juvenile justice system, above all where acquisitive and rebellious delinquency is concerned, especially in relation to the community, the family and sex. Among the middle and upper classes the stigma of delinquency is attached more to aggression and rebellion connected with automobiles and vandalism.As to the origins of social reaction ¦— the way in which an adolescent is admitted to the juvenile justice system .— the citizen reports offences against his person and property, while the police record offences against public order and morals.At the police level, the adolescent is returned to his home if it is a question of rebellion committed by a group between the ages of 12 and 15, whereas he is taken to court if his offence, reported by the citizen, is repeated and of a more serious nature. In the case of those taken to court, the adolescent is detained if he is a recidivist, and receives a summons if it is his first offence.The judges favor special measures in the case of rebelliousness, and no action at all (postponement sine die) in the case of aggression or theft by adolescents of the working class. A recidivist will be institutionalized for a serious infraction and treated within the community in the case of a less serious offence. Re-education in the community is given if the adolescent has been detained, and a fine if he has received a summons.The results clearly show that the characteristics of the delinquent acts are more important than the socioeconomic milieu in determining whatdecisions are taken. However, the socioeconomic milieu does influence admission into the juvenile justice system, as well as judicial reaction. Working-class subjects are given less attention than those from the middle and upper classes, postponement sine die is more often used in the working-class milieu, and fines, re-education within the community and institu-tionalization are more often applied to subjects of the middle and upper classes. Moreover, the margin of discretionary powers in decision making is, on the whole, rather narrow, which means that in the majority of cases, decisions can be explained by no other factors than the characteristics of the delinquent acts. This discretionary margin in decision making is narrow, both at the police and judicial levels, when a choice between particular measures must be made ; on the other hand, there is some leeway, since the judge must choose between postponement sine die and a particular measure. Finally, the course of the offence within the juvenile justice system reinforces the previous decisions through a process of amplification, which, as a consequence, penalizes working-class subjects to some extent.In short, delinquency is an adolescent phenomenon in general, but only a minority of infractions enter and continue to circulate within the juvenile justice system. The criteria for decision making are indeed socio-economic, but more often relate to the past history of the delinquent and the nature of his offence.